Upaya Meningkatkan Kesadaran Literasi Digital Pada Mahasiswa Untuk Mencapai Pembangunan Manusia Berkelanjutan - Tiara Dwi Pamungkas; Ayu Nur Intani; Ichsan Fauzi Rachman (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Advances in technology and the way we access information have an impact on reading interest causing changes in literacy culture that are important to understand. The spread of information technology that is getting easier and faster, not only brings benefits but also has a bad impact. Therefore, the need for understanding in filtering information, one of which is by increasing digital literacy. This study aims to review more thoroughly and synthesize the latest literature to provide knowledge about the development of digital literacy and efforts to increase digital literacy, especially for students. The method applied is a qualitative approach. Using the Sinta database, this study applies systematic literature review (SLR) techniques to thoroughly assess the trends and developments of Digital Literacy. This study reveals several conclusions on the main topic: In an effort to improve digital literacy in students, it can be done by developing a critical mindset, functional skills, communication and interaction, accurately sorting and evaluating information, and understanding digital culture.